Synchronization and demodulation of LoRa null port data - Lei Fang; Chen Bo; Lv Jingzhao; Li Pingan; Du Haitao; Li Su (Dianzi Jishu Yingyong, 2022)
LoRa communication technology has the characteristics of low power consumption and long distance, and has attracted more and more attention in life. However, for the underlying LoRa modulation and demodulation technology and the physical layer communication link flow, the official does not have the public technical document description, only some literature mentioned these contents. This paper improves the physical layer communication link flow by combining the LoRa modulation parameter configuration interface the official Rhode instrument with the literature. The principle of LoRa modulation and demodulation technology is described in essence, and the LoRa modulation data are collected from the Rhode instrument null port. The modulation and demodulation algorithm of LoRa literature is verified, and a synchronization algorithm of LoRa null port data is proposed. The LoRa demodulation of null port data is realized. Finally, the noise resistance performance was simulated for the LoRa modulation technique at 5 code rates. The simulation results show that the reduction of bit rate does not mean that the anti-noise ability of the system will be improved. The code rate is 4/5 with the best effect error correction, and the noise resistance performance improves by about 1 dB.